A novel SNP in promoter region of RP11-3N2.1 is associated with reduced risk of colorectal cancer. Issue 1 (January 2018) - Ye, Ding; Hu, Yunqing; Jing, Fangyuan; Li, Yingjun; Gu, Simeng; Jiang, Xiyi; Mao, Yingying; Li, Qilong; Jin, Mingjuan; Chen, Kun
Abstract Single-nucleotide polymorphisms (SNPs) in the promoter region of long intergenic non-coding RNAs (lincRNAs) could play a regulatory role in its expression level and then get involved in colorectal cancer (CRC). Thus, we conducted a two-stage case–control study to investigate the associations of Tag SNPs within the promoter region of selected lincRNAs from microarray data with risk of CRC. A total of 320 cases and 319 controls were recruited in the test set to explore the associations between 16 SNPs with no deviations from Hardy–Weinberg equilibrium (HWE) and risk of CRC. Furthermore, 501 cases and 538 controls were included as the validation set to confirm the significant associations. RP11-3N2.1 rs13230517 polymorphism was found to be negatively associated with CRC in both test set (AA vs. GG, OR = 0.68, 95% CI = 0.48–0.96) and validation set (AA vs. GG, OR = 0.76, 95% CI = 0.59–0.98). Pooled analysis showed that individuals with GA/AA genotypes had a significantly decreased risk of CRC when compared with those carrying GG genotype (OR = 0.74, 95% CI = 0.60–0.90) in the combined set. The crossover analysis revealed that rs13230517 GA/AA carriers had a decreased risk of CRC than GG carriers among non-drinkers in both test and combined set. However, no gene-environment multiplicative interactions were found on risk of CRC. Our findings suggest that rs13230517 polymorphism might participate in the pathogenesis of CRC and have the potential to be a biomarker for predicting the risk of CRC.